Normalisasi Sungai Cilemer Kabupaten Pandeglang, Banten (Studi Kasus HM 00+00 sampai HM 153+00) - Restu Wigati; Intan Afiah Rakhmatika; Woelandari Fathonah; Bambang Adhi Priyambodho; Ngakan Putu Purnaditya; Soedarsono Soedarsono (Jurnal Fondasi, 2022)
Along with changes in river conditions and population growth, rivers do not function optimally, so as a result of these changes, flooding occurs and causes many losses. Banten Province floods have impacted the community, damaging buildings, rice fields, facilities and infrastructure, and the environment, harming people's livelihoods, especially in the Cilemer River. This study aimed to determine the magnitude of the planned flood discharge for the 100-year return period, the river's capacity with the flood discharge, and the best solution to the Cilemer River's flooding problem. The flood discharge cannot be accommodated by rainfall plans of 177.137 mm, HM 00+00 to HM 153+00, with 94 cross-sectional river segments. According to the hydraulic analysis, the Cilemer River's capacity in the current conditions cannot drain the planned flood discharge, so flood control efforts are required. River normalization and embankment elevation reduced water level by 45.42 percent on average and discharged by 12.46 percent on average.